Hard alloy for complex rock stratum deep drilling and preparation method thereof

By modifying the main components of cemented carbide and introducing cobalt-iron composite powder, nitrogen-doped alumina and carbon-doped zirconia, the problems of low lateral fracture strength, low impact toughness and poor wear resistance in deep drilling of complex rock layers are solved, and the performance improvement of cemented carbide is achieved.

CN119553126AInactive Publication Date: 2025-03-04CHENGDU MINJIANG PRECISION CUTTING TOOL CO LTD
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202510129404.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the drilling of deep drilling of complex rock layers, existing cemented carbides have problems such as low lateral fracture strength, low impact toughness and poor wear resistance.

Method used

By modifying the main component of the cemented carbide, cobalt-iron composite powder is introduced, and nitrogen-doped alumina and carbon-doped zirconium dioxide are added during the preparation process. Through the synergistic action of multi-components, the lateral fracture strength and impact toughness of the cemented carbide are improved, while good wear resistance is obtained.

Benefits of technology

It significantly improves the lateral fracture strength and impact toughness of cemented carbide, and obtains good wear resistance, which is suitable for deep drilling of complex rock layers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of hard alloy materials, and particularly relates to a hard alloy for complex rock stratum deep drilling and a preparation method thereof. The hard alloy for deep drilling of the complex rock stratum is prepared by modifying the main component tungsten carbide of the hard alloy, selecting the cobalt-iron composite powder and introducing the nitrogen-doped aluminum oxide and the carbon-doped zirconium dioxide, and through the synergistic effect of multiple components, the transverse breaking strength is improved, the impact toughness is improved, and the mechanical property of the hard alloy is improved. And meanwhile, good wear resistance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cemented carbide materials, and in particular relates to a cemented carbide for deep drilling in complex rock formations and a preparation method thereof. Background Art

[0002] Downhole tools used for deep drilling in complex rock formations are not only subject to high-speed abrasive erosion from drilling fluids during downhole work, but are also often subjected to extremely harsh working conditions such as high-temperature corrosion, high-speed friction, vibration, and torsion at the bottom of the well, which makes the parts of downhole tools extremely prone to wear, and then the tools fail, thereby reducing drilling efficiency, increasing drilling costs, and causing serious downhole accidents. Cemented carbide refers to an alloy material that is sintered in a vacuum furnace or a hydrogen reduction furnace by a powder metallurgy process with high-hardness refractory metals and high-toughness bonding metals. Cemented carbide is widely used in mechanical processing and manufacturing, drilling industry, mining and metallurgy industries due to its high hardness, high strength and good wear resistance.

[0003] A Chinese patent (publication number CN114045422B) discloses a self-sharpening cemented carbide and its preparation method. In the invention, the non-uniform bonding phase Co area can be worn away by the rock first during the drilling process, so that the area composed of the hard phase WC and the uniform bonding phase Co has a sufficient blade height, and then the surface of the cemented carbide and the rock surface are in a serrated or wavy contact from a microscopic point of view, ensuring the self-sharpening performance of the drilling material, improving the actual drilling pressure, facilitating the pressing into the rock, and improving the efficiency of the drilling operation. However, the patent does not solve the problems of low transverse fracture strength, low impact toughness, and poor wear resistance of cemented carbide in the prior art, which seriously affects its actual use.

[0004] Therefore, how to modify the main components of cemented carbide and introduce functional components to improve transverse fracture strength, increase impact toughness, and obtain good wear resistance has become a direction that needs to be focused on. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a cemented carbide for deep drilling in complex rock formations and a preparation method thereof, aiming to solve the problems of low transverse fracture strength, low impact toughness and poor wear resistance of cemented carbide in the prior art.

[0006] The present invention performs modification treatment on tungsten carbide, the main component of cemented carbide, and selects cobalt-iron composite powder, and introduces nitrogen-doped alumina and carbon-doped zirconium dioxide to prepare cemented carbide for deep drilling in complex rock formations. Through the synergistic effect of multiple components, the transverse fracture strength is improved, the impact toughness is increased, and good wear resistance is obtained.

[0007] The technical solution adopted by the present invention to solve the above technical problems is as follows: The first aspect of the present invention provides a method for preparing cemented carbide for deep drilling in complex rock formations, comprising the following steps: Step S1: in parts by weight, 20-24 parts of glucose, 6-8 parts of ammonium metatungstate and 1-3 parts of gadolinium chloride are mixed evenly, 10-14 parts of deionized water and 10-14 parts of anhydrous ethanol are added and stirred for 60-80 minutes, and then the mixture is kept warm at 70-76°C for 8-10 hours to obtain a mixture, and the mixture is transferred to a box-type atmosphere furnace, heated to 880-900°C at a rate of 5°C / min in a nitrogen atmosphere, kept warm for 1-3 hours, cooled naturally to room temperature, washed with deionized water, and dried to obtain modified tungsten carbide; Step S2: by weight, 50-60 parts of modified tungsten carbide, 20-30 parts of cobalt powder, 2-6 parts of aluminum oxide and 2-4 parts of zirconium dioxide are mixed and ball-milled for 20-24 hours, vacuum dried, and sieved to obtain a mixture; Step S3: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing the mixture into a compact under a pressure of 120-180 MPa; Step S4: sintering the compact, first at 800-840° C. for 1-3 hours, then at 1300-1340° C. for 30-60 minutes, and cooling to room temperature to obtain a cemented carbide for deep drilling in complex rock formations.

[0008] The modified tungsten carbide introduces gadolinium, which can hinder the migration of tungsten carbide grain boundaries, inhibit the growth of tungsten carbide grains, and reduce the number of pores and abnormally grown tungsten carbide grains; at the same time, gadolinium as a rare earth element can reduce impurities at the grain boundaries, purify the grain boundaries and improve their wettability, increase the strength of the grain boundaries and phase boundaries, and thus improve the transverse fracture strength of the cemented carbide.

[0009] As a preferred technical solution of the present invention, the cobalt powder is a cobalt-iron composite powder; the preparation method of the cobalt-iron composite powder comprises: adding 2 to 4 parts of sodium hydroxide to 10 to 20 parts of deionized water by weight and mixing evenly, then adding 6 to 8 parts of phenol and 2 to 4 parts of formaldehyde at 40 to 44° C. for heating reaction, adjusting the pH to 7.2 to 7.4 after the heating reaction, vacuum drying to obtain an intermediate, adding 20 to 24 parts of the intermediate to 100 to 1 The mixture was stirred in 20 parts of anhydrous ethanol for 20-30 minutes, and then 4-6 parts of polyether F127 were added and stirred for 60-80 minutes. Subsequently, 0.6-0.8 parts of ferric nitrate, 1.2-1.4 parts of cobalt nitrate and 0.7-0.9 parts of acetylacetone were added and mixed evenly. The mixture was allowed to stand at 36-40°C for 10-12 hours, and the temperature was raised to 100-106°C and heated for 20-24 hours to obtain the product. The product was transferred to a tubular furnace for calcination to obtain a cobalt-iron composite powder.

[0010] As a preferred technical solution of the present invention, the conditions of the heating reaction include: temperature of 80-84° C. and time of 50-60 min.

[0011] As a preferred technical solution of the present invention, the calcination treatment conditions include: placing in a nitrogen atmosphere, a temperature of 780-800° C., and a time of 4-6 hours.

[0012] The interaction between cobalt and iron in the cobalt-iron composite powder can change the interface characteristics between tungsten carbide particles and the binding phase in the cemented carbide to a certain extent, which is beneficial to enhance the interface bonding strength, reduce stress concentration, and thus improve the overall impact toughness of the material.

[0013] As a preferred technical solution of the present invention, the alumina is nitrogen-doped alumina; the preparation method of the nitrogen-doped alumina comprises: in parts by weight, 36 to 40 parts of alumina, 16 to 20 parts of nitrogen quantum dots, 8 to 10 parts of methyltrioctylammonium chloride, 4 to 6 parts of 2-methyl-2,4-pentanediol and 2 to 4 parts of polyethylene glycol are uniformly mixed and ball-milled for 24 to 30 hours to obtain a mixed slurry; the mixed slurry is heat-treated at 760 to 800° C. for 10 to 12 hours, and after cooling to room temperature, it is crushed and ground to obtain nitrogen-doped alumina.

[0014] As a preferred technical solution of the present invention, the particle size of the aluminum oxide is 100~200nm.

[0015] As a preferred technical solution of the present invention, the preparation method of the nitrogen quantum dots comprises: adding 2 to 4 parts of 2-azidoimidazole to 16 to 18 parts of tetrahydrofuran by weight and fully dissolving them, then adding 4 to 6 parts of polyethyleneimine, and reacting at 60 to 70° C. for 20 to 24 hours; after the reaction is completed, adding 2 to 4 parts of deionized water, drying the tetrahydrofuran with a rotary evaporator, extracting with ethyl acetate, dialyzing the aqueous phase solution for 8 to 10 hours, filtering with a filter membrane, and freeze-drying the filtrate to obtain the nitrogen quantum dots.

[0016] Nitrogen quantum dots are introduced into nitrogen-doped alumina. As a nanomaterial, nitrogen quantum dots can form a protective film on the contact surface and play a self-lubricating role to a certain extent. This film can reduce the direct friction contact loss of the metal, thereby effectively reducing the friction coefficient of cemented carbide.

[0017] As a preferred technical solution of the present invention, the zirconium dioxide is carbon-doped zirconium dioxide; the preparation method of the carbon-doped zirconium dioxide comprises: adding 10 to 12 parts of zirconium oxychloride, 6 to 8 parts of carbon dots and 4 to 6 parts of polyethylene glycol to 100 to 110 parts of deionized water by weight and mixing them evenly, adding 16 to 20 parts of a 20% by mass sulfuric acid solution at 70 to 80° C. to obtain a mixed solution, heating the mixed solution to 140 to 150° C. for hydrothermal reaction for 6 to 8 hours, cooling to room temperature, adding 4 to 8 parts of ammonia water to adjust the pH to 7.4 to 7.8, centrifuging, washing, drying, and calcining to obtain carbon-doped zirconium dioxide.

[0018] As a preferred technical solution of the present invention, the preparation method of the carbon dots includes: adding 4 to 8 parts of split wood to 160 to 180 parts of deionized water by weight and stirring for 40 to 50 minutes, conducting a thermal reaction at 190 to 200°C for 6 to 8 hours, naturally cooling after the reaction is completed, centrifuging to obtain a reaction liquid, filtering the reaction liquid with a microporous filter membrane, and freeze-drying to obtain carbon dots.

[0019] The carbon dots in carbon-doped zirconium dioxide can form a graphite-like structured film on the contact surface, which can provide a smoother surface and have good lubrication properties, which can significantly reduce wear and reduce the friction coefficient of cemented carbide.

[0020] A second aspect of the present invention provides a cemented carbide for deep drilling in complex rock formations prepared by the method described in the first aspect.

[0021] Compared with the prior art, the present invention has the following beneficial effects: (1) The cobalt-iron composite powder of the present invention is prepared by an evaporation-induced self-assembly method, has a mesoporous structure and can serve as a carrier of other atoms. During the preparation of cemented carbide, the rare earth element gadolinium in the modified tungsten carbide is easily enriched in the mesoporous structure of the cobalt-iron composite powder. At the same time, the nitrogen quantum dots in the nitrogen-doped alumina and the carbon dots in the carbon-doped zirconium dioxide will migrate and form nitrogen carbides at high temperatures. Through the synergistic effect of multiple components, the transverse fracture strength and impact toughness of the cemented carbide material are increased, and good wear resistance is obtained.

[0022] (2) The modified tungsten carbide of the present invention introduces gadolinium, which can hinder the migration of tungsten carbide grain boundaries, inhibit the growth of tungsten carbide grains, and reduce the number of pores and abnormally grown tungsten carbide grains; at the same time, gadolinium as a rare earth element can reduce impurities at the grain boundaries, purify the grain boundaries and improve their wettability, increase the strength of the grain boundaries and phase boundaries, and thus improve the transverse fracture strength of the cemented carbide.

[0023] (3) The interaction between cobalt and iron in the cobalt-iron composite powder of the present invention can change the interface characteristics between the tungsten carbide particles and the binder phase in the cemented carbide to a certain extent, which is beneficial to enhancing the interface bonding strength and reducing stress concentration, thereby improving the overall impact toughness of the material.

[0024] (4) Nitrogen quantum dots are introduced into the nitrogen-doped alumina of the present invention. As a nanomaterial, nitrogen quantum dots can form a protective film on the contact surface and play a self-lubricating role to a certain extent. This film can reduce the direct friction contact loss of the metal, thereby effectively reducing the friction coefficient of the cemented carbide and improving the wear resistance.

[0025] (5) The carbon dots in the carbon-doped zirconium dioxide of the present invention can form a graphite-like structured film on the contact surface, which can provide a smoother surface and has good lubrication properties, which can significantly reduce wear and reduce the friction coefficient of cemented carbide. DETAILED DESCRIPTION

[0026] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0027] The sources of some components in the embodiments and comparative examples are as follows: Tungsten carbide, CAS No. 12070-13-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Cobalt powder, CAS No. 7440-48-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Alumina I, model PAT-G10A, particle size 100 nm, purchased from Nanjing Baoket New Materials Co., Ltd.; Alumina II, model XFI08, particle size 15 nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; Alumina III, model DCA-10W, particle size 10 μm, purchased from Dongguan Dongchao New Materials Technology Co., Ltd.; Zirconium dioxide, CAS No. 1314-23-4, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Glucose, CAS No. 50-99-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ammonium metatungstate, CAS No. 14311-52-5, purchased from Zhongshan Dixin Chemical Co., Ltd.; Gadolinium chloride, CAS No. 19423-81-5, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Phenol, CAS No. 108-95-2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Formaldehyde, CAS No. 50-00-0, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Polyether F127, CAS No. 9003-11-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Ferric nitrate, CAS No. 7782-61-8, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Cobalt nitrate, CAS No. 10026-22-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Acetylacetone, CAS No. 123-54-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Methyltrioctylammonium chloride, CAS No. 63393-96-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.; 2-Methyl-2,4-pentanediol, CAS No. 107-41-5, purchased from Sinopharm Chemical Reagent Co., Ltd.; Polyethylene glycol, product number P103725, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; 2-Azimidazole, CAS No. 56751-68-9, purchased from Tianjin Yankai Technology Co., Ltd.; Tetrahydrofuran, CAS No. 109-99-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Polyethyleneimine, product number E107079, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; Ethyl acetate, CAS No. 141-78-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Dividing wood was purchased from Mingjie Biotechnology Co., Ltd.; Zirconium oxychloride, CAS No. 7699-43-6, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Sulfuric acid, CAS No. 7664-93-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.; Ammonia water, CAS No. 1336-21-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0028] Preparation of cobalt-iron composite powder: In parts by weight, 4 parts of sodium hydroxide are added to 20 parts of deionized water and mixed evenly, then 8 parts of phenol and 4 parts of formaldehyde are added at 40°C for heating reaction (temperature is 80°C, time is 60 minutes), pH is adjusted to 7.4 after heating reaction, and vacuum drying is performed to obtain an intermediate, 24 parts of the intermediate are added to 120 parts of anhydrous ethanol and stirred for 30 minutes, then 6 parts of polyether F127 are added and stirred for 80 minutes, then 0.8 parts of ferric nitrate, 1.4 parts of cobalt nitrate and 0.9 parts of acetylacetone are added and mixed evenly, and the mixture is allowed to stand at 40°C for 10 hours, heated to 100°C and heated for 24 hours to obtain a product, and the product is transferred to a tubular furnace for calcination treatment (placed in a nitrogen atmosphere, temperature is 800°C, time is 4 hours) to obtain a cobalt-iron composite powder.

[0029] Preparation of nitrogen-doped alumina: (1) In parts by weight, 4 parts of 2-azidoimidazole were added to 18 parts of tetrahydrofuran and fully dissolved, and then 6 parts of polyethyleneimine were added and reacted at 70°C for 20 hours; after the reaction was completed, 4 parts of deionized water were added, and the tetrahydrofuran was dried by rotary evaporator, and then extracted with ethyl acetate, and the aqueous phase solution was dialyzed for 10 hours, filtered with a filter membrane, and the filtrate was freeze-dried to obtain the nitrogen quantum dots. (2) In parts by weight, 40 parts of alumina I (model PAT-G10A, particle size 100nm), 20 parts of nitrogen quantum dots, 10 parts of methyltrioctylammonium chloride, 6 parts of 2-methyl-2,4-pentanediol and 4 parts of polyethylene glycol were mixed evenly and ball-milled for 30 hours to obtain a mixed slurry; the mixed slurry was heat-treated at 800°C for 10 hours, and then crushed and ground after cooling to room temperature to obtain nitrogen-doped alumina.

[0030] Preparation of carbon-doped zirconium dioxide: (1) By weight, 8 parts of split wood were added to 180 parts of deionized water and stirred for 50 minutes, and a thermal reaction was carried out at 190°C for 8 hours. After the reaction was completed, the mixture was naturally cooled and centrifuged to obtain a reaction solution, which was filtered with a microporous filter membrane and freeze-dried to obtain carbon dots. (2) By weight, 12 parts of zirconium oxychloride, 8 parts of carbon dots and 6 parts of polyethylene glycol were added to 110 parts of deionized water and mixed evenly, and 20 parts of a 20% sulfuric acid solution were added at 80°C to obtain a mixed solution, and the mixed solution was heated to 150°C for a hydrothermal reaction for 6 hours, cooled to room temperature, and 8 parts of ammonia water were added to adjust the pH to 7.8, centrifuged, washed, dried, and calcined to obtain carbon-doped zirconium dioxide.

[0031] Example 1 This embodiment provides a method for preparing cemented carbide for deep drilling in complex rock formations, comprising the following steps: Step S1: In parts by weight, 24 parts of glucose, 8 parts of ammonium metatungstate and 3 parts of gadolinium chloride are mixed evenly, 14 parts of deionized water and 14 parts of anhydrous ethanol are added and stirred for 80 minutes, and then the mixture is kept warm at 76°C for 8 hours to obtain a mixture, and the mixture is transferred to a box-type atmosphere furnace, heated to 900°C at a rate of 5°C / min in a nitrogen atmosphere and kept warm for 1 hour, cooled naturally to room temperature, washed with deionized water, and dried to obtain modified tungsten carbide; Step S2: by weight, 60 parts of modified tungsten carbide, 30 parts of cobalt-iron composite powder, 6 parts of nitrogen-doped alumina and 4 parts of carbon-doped zirconium dioxide are mixed and ball-milled for 24 hours, vacuum dried, and sieved to obtain a mixture; Step S3: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing the mixture into a compact under a pressure of 180 MPa; Step S4: sintering the compact, first at 840° C. for 1 hour, then at 1340° C. for 30 minutes, and cooling to room temperature to obtain a cemented carbide for deep drilling in complex rock formations.

[0032] Example 2 This embodiment provides a method for preparing cemented carbide for deep drilling in complex rock formations, comprising the following steps: Step S1: in parts by weight, 20 parts of glucose, 6 parts of ammonium metatungstate and 1 part of gadolinium chloride are mixed evenly, 10 parts of deionized water and 10 parts of anhydrous ethanol are added and stirred for 60 minutes, and then the mixture is kept at 70°C for 10 hours to obtain a mixture, and the mixture is transferred to a box-type atmosphere furnace, heated to 880°C at a rate of 5°C / min in a nitrogen atmosphere and kept for 3 hours, cooled naturally to room temperature, washed with deionized water, and dried to obtain modified tungsten carbide; Step S2: by weight, 50 parts of modified tungsten carbide, 20 parts of cobalt-iron composite powder, 2 parts of nitrogen-doped alumina and 2 parts of carbon-doped zirconium dioxide are mixed and ball-milled for 20 hours, vacuum dried, and sieved to obtain a mixture; Step S3: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing the mixture into a compact under a pressure of 120 MPa; Step S4: sintering the compact, first at 800° C. for 3 hours, then at 1300° C. for 60 minutes, and cooling to room temperature to obtain a cemented carbide for deep drilling in complex rock formations.

[0033] Example 3 This embodiment provides a method for preparing cemented carbide for deep drilling in complex rock formations, comprising the following steps: Step S1: in parts by weight, 22 parts of glucose, 7 parts of ammonium metatungstate and 2 parts of gadolinium chloride are mixed evenly, 12 parts of deionized water and 12 parts of anhydrous ethanol are added and stirred for 70 minutes, and then the mixture is kept warm at 72°C for 9 hours to obtain a mixture, and the mixture is transferred to a box-type atmosphere furnace, heated to 890°C at a rate of 5°C / min in a nitrogen atmosphere and kept warm for 2 hours, cooled naturally to room temperature, washed with deionized water, and dried to obtain modified tungsten carbide; Step S2: by weight, 55 parts of modified tungsten carbide, 25 parts of cobalt-iron composite powder, 4 parts of nitrogen-doped alumina and 3 parts of carbon-doped zirconium dioxide are mixed and ball-milled for 22 hours, vacuum dried, and sieved to obtain a mixture; Step S3: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing it into a compact under a pressure of 150 MPa; Step S4: sintering the compact, first at 820° C. for 2 hours, then at 1320° C. for 40 minutes, and cooling to room temperature to obtain a cemented carbide for deep drilling in complex rock formations.

[0034] Comparative Example 1 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that commercially available tungsten carbide is used instead of modified tungsten carbide.

[0035] Comparative Example 2 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that commercially available cobalt powder is used instead of cobalt-iron composite powder.

[0036] Comparative Example 3 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that aluminum oxide I is used instead of nitrogen-doped aluminum oxide.

[0037] Comparative Example 4 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that aluminum oxide II is used instead of aluminum oxide I to prepare nitrogen-doped aluminum oxide.

[0038] Comparative Example 5 This comparative example provides a method for preparing cemented carbide, which differs from Example 1 in that aluminum oxide III is used instead of aluminum oxide I to prepare nitrogen-doped aluminum oxide.

[0039] Comparative Example 6 This comparative example provides a method for preparing a cemented carbide, which differs from Example 1 in that commercially available zirconium dioxide is used instead of carbon-doped zirconium dioxide.

[0040] The performance of the cemented carbide provided in the above embodiments and comparative examples was tested, and the testing method was as follows: (1) Transverse rupture strength test: Test according to the requirements of GB / T 3851-2015 Method for determination of transverse rupture strength of cemented carbide.

[0041] (2) Impact toughness test: Test according to the requirements of GB / T 229-2020 Metallic Materials Charpy Pendulum Impact Test Method.

[0042] (3) Friction coefficient test: Test according to the requirements of “YB / T 4286-2012 Test method for friction coefficient of metal sheets and strips”.

[0043] The above performance test data is shown in Table 1.

[0044] Table 1 Performance test results Transverse rupture strength (MPa) Impact toughness (J) Friction coefficient Example 1 4218 324 0.32 Example 2 4205 307 0.41 Example 3 4212 315 0.37 Comparative Example 1 3649 228 0.86 Comparative Example 2 3668 243 0.72 Comparative Example 3 3656 232 0.81 Comparative Example 4 3944 286 0.53 Comparative Example 5 3938 281 0.58 Comparative Example 6 3661 237 0.75 From the above content, it can be seen that the present invention modifies tungsten carbide, the main component of cemented carbide, and selects cobalt-iron composite powder, and introduces nitrogen-doped alumina and carbon-doped zirconium dioxide to prepare cemented carbide for deep drilling in complex rock formations (Examples 1~3), which has a transverse rupture strength of 4205~4218MPa, an impact toughness of 307~324J, and a friction coefficient of 0.32~0.41.

[0045] Compared with Example 1, using commercially available tungsten carbide instead of modified tungsten carbide, the transverse rupture strength is reduced, the impact toughness is reduced, and the friction coefficient is increased (Comparative Example 1); Compared with Example 1, using commercially available cobalt powder instead of cobalt-iron composite powder, the transverse rupture strength is reduced, the impact toughness is reduced, and the friction coefficient is increased (Comparative Example 2); Compared with Example 1, using aluminum oxide I instead of nitrogen-doped aluminum oxide, the transverse rupture strength is reduced, the impact toughness is reduced, and the friction coefficient is increased (Comparative Example 3); Compared with Example 1, using aluminum oxide II instead of aluminum oxide I for nitrogen-doped aluminum oxide Preparation, due to the small particle size of aluminum oxide II, the modification effect is not good, the transverse rupture strength is reduced, the impact toughness is reduced, and the friction coefficient is increased (Comparative Example 4); compared with Example 1, aluminum oxide III is used to replace aluminum oxide I for the preparation of nitrogen-doped aluminum oxide. Due to the large particle size of aluminum oxide III, the modification effect is not good, the transverse rupture strength is reduced, the impact toughness is reduced, and the friction coefficient is increased (Comparative Example 5); compared with Example 1, commercially available zirconium dioxide is used to replace carbon-doped zirconium dioxide, the transverse rupture strength is reduced, the impact toughness is reduced, and the friction coefficient is increased (Comparative Example 6).

[0046] In summary, the present invention modifies tungsten carbide, the main component of cemented carbide, and selects cobalt-iron composite powder, and introduces nitrogen-doped alumina and carbon-doped zirconium dioxide to prepare cemented carbide for deep drilling in complex rock formations. Through the synergistic effect of multiple components, the transverse fracture strength is improved, the impact toughness is increased, and good wear resistance is obtained.

Claims

1. A method for preparing cemented carbide for deep drilling in complex rock formations, characterized in that: The following steps are involved: Step S1: in parts by weight, 20-24 parts of glucose, 6-8 parts of ammonium metatungstate and 1-3 parts of gadolinium chloride are mixed uniformly, 10-14 parts of deionized water and 10-14 parts of anhydrous ethanol are added and stirred for 60-80 minutes, and then the mixture is kept warm at 70-76°C for 8-10 hours to obtain a mixture, and the mixture is transferred to a box-type atmosphere furnace, heated to 880-900°C at a rate of 5°C / min in a nitrogen atmosphere, kept warm for 1-3 hours, cooled naturally to room temperature, washed with deionized water, and dried to obtain modified tungsten carbide; Step S2: by weight, 50-60 parts of modified tungsten carbide, 20-30 parts of cobalt powder, 2-6 parts of aluminum oxide and 2-4 parts of zirconium dioxide are mixed and ball-milled for 20-24 hours, vacuum dried, and sieved to obtain a mixture; Step S3: wax-adding, grinding and granulating the mixture in a sealed state, and then pressing the mixture into a compact under a pressure of 120-180 MPa; Step S4: sintering the compact, first at 800-840° C. for 1-3 hours, then at 1300-1340° C. for 30-60 minutes, and cooling to room temperature to obtain a cemented carbide for deep drilling in complex rock formations.

2. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 1, characterized in that: The cobalt powder is a cobalt-iron composite powder; The preparation method of the cobalt-iron composite powder comprises: adding 2-4 parts of sodium hydroxide to 10-20 parts of deionized water by weight and mixing them evenly, then adding 6-8 parts of phenol and 2-4 parts of formaldehyde at 40-44° C. for heating reaction, adjusting the pH to 7.2-7.4 after the heating reaction, vacuum drying to obtain an intermediate, adding 20-24 parts of the intermediate to 100-120 parts of anhydrous ethanol and stirring for 20-30 minutes, then adding 4-6 parts of polyether F127 and stirring for 60-80 minutes, then adding 0.6-0.8 parts of ferric nitrate, 1.2-1.4 parts of cobalt nitrate and 0.7-0.9 parts of acetylacetone and mixing them evenly, standing at 36-40° C. for 10-12 hours, heating to 100-106° C. and heating for 20-24 hours to obtain a product, and transferring the product to a tubular furnace for calcination treatment to obtain the cobalt-iron composite powder.

3. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 2, characterized in that: The conditions of the heating reaction include: temperature of 80-84° C. and time of 50-60 min.

4. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 2, characterized in that: The calcination treatment conditions include: placing in a nitrogen atmosphere, a temperature of 780-800° C., and a time of 4-6 hours.

5. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 1, characterized in that: The aluminum oxide is nitrogen-doped aluminum oxide; The preparation method of the nitrogen-doped alumina comprises: mixing 36-40 parts of alumina, 16-20 parts of nitrogen quantum dots, 8-10 parts of methyl trioctylammonium chloride, 4-6 parts of 2-methyl-2,4-pentanediol and 2-4 parts of polyethylene glycol in parts by weight, and then ball-milling and dispersing them for 24-30 hours to obtain a mixed slurry; heat-treating the mixed slurry at 760-800° C. for 10-12 hours, and crushing and grinding the mixed slurry after cooling to room temperature to obtain nitrogen-doped alumina.

6. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 5, characterized in that: The particle size of the aluminum oxide is 100-200 nm.

7. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 5, characterized in that: The preparation method of the nitrogen quantum dots comprises: adding 2 to 4 parts of 2-azidoimidazole to 16 to 18 parts of tetrahydrofuran by weight to fully dissolve, then adding 4 to 6 parts of polyethyleneimine, and reacting at 60 to 70° C. for 20 to 24 hours; after the reaction is completed, adding 2 to 4 parts of deionized water, drying the tetrahydrofuran with a rotary evaporator, extracting with ethyl acetate, dialyzing the aqueous solution for 8 to 10 hours, filtering with a filter membrane, and freeze-drying the filtrate to obtain the nitrogen quantum dots.

8. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 1, characterized in that: The zirconium dioxide is carbon-doped zirconium dioxide; The preparation method of the carbon-doped zirconium dioxide comprises: adding 10 to 12 parts of zirconium oxychloride, 6 to 8 parts of carbon dots and 4 to 6 parts of polyethylene glycol to 100 to 110 parts of deionized water, mixing them evenly, adding 16 to 20 parts of a 20% by mass sulfuric acid solution at 70 to 80° C. to obtain a mixed solution, heating the mixed solution to 140 to 150° C. for hydrothermal reaction for 6 to 8 hours, cooling to room temperature, adding 4 to 8 parts of ammonia water to adjust the pH to 7.4 to 7.8, centrifuging, washing, drying and calcining to obtain the carbon-doped zirconium dioxide.

9. The method for preparing a cemented carbide for deep drilling in complex rock formations according to claim 8, characterized in that: The preparation method of the carbon dots comprises: adding 4 to 8 parts of split wood to 160 to 180 parts of deionized water by weight and stirring for 40 to 50 minutes, performing a thermal reaction at 190 to 200° C. for 6 to 8 hours, cooling naturally after the reaction is completed, centrifuging to obtain a reaction solution, filtering the reaction solution with a microporous filter membrane, and freeze-drying to obtain carbon dots.

10. A cemented carbide for deep drilling in complex rock formations, characterized in that: Prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A self-sharpening cemented carbide and its preparation method

    CN114045422B

  • Method for manufacturing hard alloy

    CN103789565A

  • Hard alloy cutter material used for processing aluminum alloy and preparing method thereof

    CN107099720A

  • Preparation method of nitrogen-doped ordered mesoporous carbon supported transition metal nanoparticle catalyst

    CN108355694A

  • Ceramic metal roll-ring

    CN1174764A